LAGRANGE FUNCTION FOR THE LAYERED SUPERCONDUCTOR SAMPLES OF FINITE SIZE - Bukhtatyi , A.; Maizelis , Z.A.; Yampol’skii, V.A. (Reports of the National Academy of Sciences of Ukraine, 2024)
The theoretical investigation of Josephson plasma wave propagation in confined samples of a layered superconductor was conducted using the Lagrangian approach. Based on fundamental experimental results, an expression for the Lagrange function governing the coupled degrees of freedom of the order parameter phase in the layers of the sample and the electromagnetic field was derived. It is shown that, in k-space, the Lagrange function represents of a counted set of independent contributions corresponding to various possible waveguide modes in the sample, categorized as ordinary and extraordinary modes. Dispersion dependences for the modes were obtained. The results of this study can be applied to the construction of electronic devices in the Terahertz frequency range.